Designing Fieldwork Material in Geography Learning through Potential Tourism and Landscape Feature (Case Study in Srigonco Village) - Sahrina, Alfi; Rosyida, Fatiya; Wirahayu, Yuswanti Ariani; Mahanani, Putri; Ngoc, Ho Nhu (Geosfera Indonesia, 2025)
The landscape appearance of Srigonco Village is unique. This uniqueness can be used as a means of learning geography. This study aims to analyze the tourism potential and landscape appearance of Srigonco Village as a means of supporting geography learning. The method used is a field survey by making a working map which is then used to identify tourism potential and landscape appearances. Analysis of natural tourism potential was carried out using neighborhood analysis and analysis of landscape appearance using qualitative descriptive. The study's findings indicate that the tourism potential of Srigonco village is dispersed, with clusters of caves and ponor in the center, an elongated area to the south with beaches, and scattered springs around the community. In addition, the research location has fluvial, karst, and marine landscape elements such as caves, rivers, beaches, waterfalls, and biodiversity preservation, can also be utilised for natural tourism. Srigonco Village's topography can be utilized to teach geography, particularly in the study of geomorphology, hydrology, biogeography, disasters, tourism, and socio-culture. The application of geography learning can be carried out through field activities, research, or project-based learning to provide students with the opportunity to learn directly from the environment.